Congenital Abnormalities of the Temporomandibular Joint - single conditions - Anna Stangret; Agata Mularczyk; Angelika Szczęśniak; Katarzyna Topczewska; Karolina Rogulska (Kazimierz Wielki University, 2020)
Temporomandibular joint (TMJ), due to its morphological structure, is a bicondylar joint, coupled in every movement. Intensive development of TMJ occurs in the early fetal period. Diseases of the temporomandibular joints differ in etiology and symptoms. The dysfunction of temporomandibular joint may lead to many problems connected with disorders of masseter muscles and <span